SPICE Engine Analysis and Circuit Simulation Application Development - Bing Chen; Gang Lu; Yuehai Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Electrical design automation plays an important role in nowadays electronic industry. Various commercial Simulation Program with Integrated Circuit Emphasis (SPICE) packages, such as pSpice Or CAD, have become the standard computer program for electrical simulation, with numerous copies in use worldwide. The customized simulation software with copyright need the understanding and using of SPICE engine which was open-source shortly after its birth. The inner workings of SPICE, including algorithms, data structure and code structure of SPICE were analyzed, and a engine package and application development approach were proposed. The experiments verified its feasibility and accuracy.